Global pattern of historical and future changes in rapid temperature variability. (22nd December 2020) - Xu, Zhongfeng; Huang, Fang; Liu, Qi; Fu, Congbin
Abstract: Day-to-day (DTD) temperature variation reflects a rapid weather variability, which significantly affects human health and ecosystems. However, while a few of studies have addressed certain regional variations, no global pattern of rapid temperature variability has yet been investigated. Here, using global daily temperature observation data, we present a study of the worldwide spatial heterogeneity of rapid temperature variability and its long-term trends over the past 60 years. We found a significant decline in northern mid and high latitudes in boreal winter but a significant increase in the Arctic coast, South China and Australia in boreal summer during the study period. Using observational data and Coupled Model Intercomparison Project Phase 5 (CMIP5) multi-model ensemble simulations, we further demonstrate that the human-caused increase in greenhouse gases (GHGs) concentration leads to a significant change in meridional temperature gradient, which in turn results in the observed decline of rapid temperature variability in the mid and high latitudes and the increase in rapid temperature variability in Arctic Coast in summer. In contrast, human-induced increase in GHGs and aerosol accounts for approximately one third and two third of the decline of rapid temperature variability in North China in boreal summer, respectively. However, the increase in summer rapid temperature variability in southern China appears to be primarily associated with the long-term internal climate variability. It is further shown that, based on the CMIP5 multi-model ensemble simulations, the projected rapid temperature variability shows a significant decrease in the high latitudes in winter but a slight increase in tropical zones by the end of this century. These findings clearly reveal an important role of human activities on the historical and future rapid temperature variability.